A Highly Efficient CuCl2-Catalyzed C–S Coupling of Aryl Iodides with Tetraalkylthiuram Disulfides: Synthesis of Aryl Dithiocarbamates - Cao, Qiang; Peng, Han-Ying; Cheng, Yu; Dong, Zhi-Bing (Synthesis, 2018)
A highly efficient copper(II)-catalyzed C–S cross-coupling reaction of aryl iodides with tetraalkylthiuram disulfides was developed. With only 1 mol% of CuCl2 as catalyst, zinc powder as reductant, and K2CO3 as base, aryl iodides reacted with tetraalkylthiuram disulfides in DMSO furnishing the corresponding aryl dithiocarbamates in good to excellent yields. This protocol is an improvement of previous work, it features convenient performance, low addition of catalyst, no requirement for any ligand, and provides good yields. The method has a broad substrate scope and uses cheap and readily available starting materials.
Keywords: coupling; aryl iodide; disulfide; synthesis; dithiocarbamate